KINERJA PRODUKSI DAN KELANGSUNGAN HIDUP IKAN GURAMI (Osphronemus goramy) YANG DIBERI DOSIS INFUSA TEMULAWAK (Curcuma xanthoriza Roxb) - Pribadi, Henki Agusan; Yusanti, Indah Anggraini; Sofian, Sofian; Saputra, Fazril (Universitas Teuku Umar, 2021)
This study aimed to evaluate the effect of dietary curcuma infusion supplementation on growth performance and survival rate in giant gouramy. This study used a Completely Randomized Design (CRD) with four treatments and three replications. The treatments tested were giving different doses of curcuma infusion, 0.2 g (P1), 0.4 g (P2), 0.6 g (P3), 0.8 g (P4). The experimental fish used were giant gourami with an average body weight of 0.28 ± 0.01 g which were reared for 30 days in 40x30x25 cm3 sized plastic box containing 20 L of water. Feed was given at satiation method twice a day, at 08.00 and 16.00 pm. The research parameters observed include Weight and Length Growth Rate, Survival Rate, and water quality. The results showed that the dietary curcuma infusion supplementation was able to increase the growth performance and survival rate of giant gouramy. Curcuma infusion dose of 0.8 g resulted in the best growth performance and survival which was not significantly different between treatments. Water quality parameters during maintenance are still in optimal conditions for fish growth.